PERAN ORGANISASI ALUMNI DALAM KEMAJUAN PONDOK PESANTREN: STUDI DI PONDOK PESANTREN BAHRUL ULUM AL-MURSYIDI KOTA TASIKMALAYA - Agus Samsudin (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2026)
This study aims to determine how the role of alumni organizations in the progress of pesantren in the Bahrul Ulum Al-Mursyidi Islamic boarding school in Tasikmalaya City. This research is a qualitative research with analytical descriptive method. Data collection techniques were carried out through interviews and literature. The subjects in this study were several organizational administrators of the Al-Mursyidi and Al-Fauziyah Alumni Association (HANIFA) Bahrul Ulum Al-Mursyidi Islamic Boarding School Tasikmalaya City. Data analysis was carried out by selecting the data obtained and then collected for analysis and conclusions drawn. The findings in this study are that the purpose of the formation of an alumni organization called HANIFA is to establish a relationship between fellow alumni and pesantren and to become a forum for alumni management for the advancement of the pesantren as a sign of reciprocation and the love of alumni to the pesantren. As an organization, HANIFA has a management structure, work program, and so on like an organization, only that its Statutes and bylaws (AD-ART) have not yet found a point of standard clarity. In relation to the Progress of Islamic Boarding Schools, HANIFA has a fairly influential role in terms of ideas or even financial ideas. Therefore, for every Islamic boarding school it is necessary to form an alumni organization to support the progress of the pesantren.